Determinants of Unequal Access to and Quality of Education in Indonesia - Tatang Muttaqin (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2018)
Indonesian government simultaneously improves access to and quality of education for all citizens. Although its efforts had a noticeable impact, many of the targets to improve access to and quality of education nevertheless, still have not been achieved and education inequality is still persistent. Using a multilevel multi-resource framework, this article comprehends some of the mechanisms behind the unequal access to and quality of education. It suggests that the impact of and interplays between human, social, economic, political and infrastructural capital at the individual, household, school, community and government level are important on inequality in access to and quality of education in Indonesia. For instance, family factors, such as wealth, education investment and educational background also reduce the likelihood that children are out of school; reciprocity can compensate low-income families for sending their children to preschool as a within level cross resource effect; living in a higher trust strengthen the effect of association on preschool participation as a between level single resource effect; residing in urban area reinforces the effect of associations but it weakens the effect of reciprocity on preschool participation as a between level cross resource effect consists of urbanization. In terms of decentralization, the length of schooling slightly increased but progress in the length of schooling slightly decreased after decentralization; even though student achievement and achievement gaps are strongly determined by student and family characteristics, the results show that differences between school tracks and streams also play an important role.